(untitled) (Bangladesh Journal of Medicine, 2024)
Background: A growing body of research has implicated lower levels of vitamin D in the pathogenesis of neurological and psychiatric disorders including obsessive-compulsive disorder (OCD). The main of this study was to investigate the relationship between vitamin D levels and OCD. Methodology: This meta-analysis follows the PRISMA guidelines and utilizes PubMed, Scopus, Web of Science, and Lens databases without temporal constraints. Six pertinent studies were selected to ensure methodological consistency and robustness in our analysis. Data were pooled using a Random-Effects Model to estimate the standard mean difference (SMD) for evaluation of the strength of association analyses. Result: Our analysis revealed a noteworthy reduction in vitamin D levels among individuals with OCD compared to controls (SMD = -0.603, 95% CI = -0.8001 to -0.4053, p < 0.001, I2 = 50.86%; Q statistic p = 0.093). Conclusion: These findings underscore the significant impact of vitamin D in the pathogenesis of OCD, suggesting its potential role in both the prevention and treatment of this psychiatric disorder. However, despite the compelling evidence presented, further studies are warranted to refine our understanding and draw more precise conclusions regarding the intricate interplay between vitamin D levels and OCD. Bangladesh J Medicine 2024; 35: 156-166